2019
DOI: 10.1002/pa.1972
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and its impacts on Indian agriculture: An Econometric analysis

Abstract: This study assessed the climate change impacts on land productivity for major food and nonfood grain crops in India. We compiled data for 50 years (1967–2016) using 15 crops across India to estimate the variation of agriculture production for each crop by different variables such as temperature and rainfall estimation. Our results indicate that land productivity decreases with an increase in annual average temperature in most of the crops. The adverse impact of climate change on agricultural production indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…This nding is similar to those of Loum and Fogarassy (2015), Dasgupta (2013), Mishra and Sahu (2014), Brown et al (2010), Akram (2012), Praveen and Sharma (2019b), and Attiaoui and Boufateh, 2019).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This nding is similar to those of Loum and Fogarassy (2015), Dasgupta (2013), Mishra and Sahu (2014), Brown et al (2010), Akram (2012), Praveen and Sharma (2019b), and Attiaoui and Boufateh, 2019).…”
Section: Resultssupporting
confidence: 87%
“…Most of the researchers have used temperature and rainfall as a proxy for climate change. Many of the studies are country-speci c (Dumrul and Kilicarslan, 2017;Zaied and Zouabi, 2015;Praveen and Sharma, 2019b;Attiaoui and Boufateh, 2019;Onour, 2019;Chandio et al, 2020a;Chandio et al, 2020bAhsan et al, 2019. It is also found that there is a limited number of studies on the relationship between climate change and cereal production.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For the country as a whole, the number of grid points shown with changing temperature pattern are greater than precipitation due to rising warm climatic conditions. Praveen and Sharma recently evaluated the historical variation of crop productivity using multiple regression analysis based on precipitation and temperature 56 . They concluded that crop production (tea, jowar, maize, ragi, sugarcane, and wheat) has reduced over the period 1967-2016, majorly due to increased temperature.…”
Section: Changing Pattern Of Precipitation and Temperature Long-term Trends For Every Grid Point Acrossmentioning
confidence: 99%
“…The developing nations are more vulnerable than developed countries due to more extensive dependence on agriculture sector for livelihood, lack of technological advancement and lack of adaptation policies of climate change on agriculture production (Praveen & Sharma, 2020;Warsame, 2021). However, Chandio et al, (2021) stated that the increase in temperature and financial development, respectively has negative and positive impact on cereal production in Pakistan.…”
Section: Introductionmentioning
confidence: 99%